Вопрос о приведении абстрактных существительных в толковом словаре каракалпакского языка и его совершенствовании - Даулетбаев, М (SCIENCE and SOCIETY, 2025)
The article considers the issue of lexicographic interpretation of abstract nouns. This issue is relevant from the point of view of the tasks of preserving and developing the national language. The research is aimed at this direction through the analysis of explanatory dictionaries of the Karakalpak language.
Keywords: dictionary; language; abstract nouns; litter; article; Karakalpak language; lexeme; explanatory dictionary; synonym; capital word